2003
DOI: 10.1093/her/18.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the potential of teachable moments: the case of smoking cessation

Abstract: The label 'teachable moment' (TM) has been used to describe naturally occurring health events thought to motivate individuals to spontaneously adopt risk-reducing health behaviors. This manuscript summarizes the evidence of TMs for smoking cessation, and makes recommendations for conceptual and methodological refinements to improve the next generation of related research. TM studies were identified for the following event categories: office visits, notification of abnormal test results, pregnancy, hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
847
3
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,006 publications
(893 citation statements)
references
References 109 publications
31
847
3
12
Order By: Relevance
“…Because cancer survivors seem amenable to making positive changes in their lifestyles to improve their health, it has been suggested that the diagnosis of cancer could serve as a 'teachable moment' for making health behavior changes [25]. In terms of cancer, a 'teachable moment' would provide an opportunity for targeted health programs to take advantage of these moments to improve the health and well-being of cancer survivors [8,18,29,34]. More research is needed, however, examining variables that may be associated with changing health behavior so that more targeted and effective health programs can be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Because cancer survivors seem amenable to making positive changes in their lifestyles to improve their health, it has been suggested that the diagnosis of cancer could serve as a 'teachable moment' for making health behavior changes [25]. In terms of cancer, a 'teachable moment' would provide an opportunity for targeted health programs to take advantage of these moments to improve the health and well-being of cancer survivors [8,18,29,34]. More research is needed, however, examining variables that may be associated with changing health behavior so that more targeted and effective health programs can be developed.…”
Section: Introductionmentioning
confidence: 99%
“…The medical encounter provides a window of opportunity to access smokers who otherwise may not seek assistance with quitting, and provides a teachable moment whereby smokers may be more receptive to messages about health risks (McBride, Emmons, & Lipkus, 2003). Metaanalyses have shown that patients who receive counseling by physicians or nurses are 1.5 to 2 times more likely to quit than those who receive usual care (Fiore, 2000;Rice & Stead, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Drawing from the health belief model, a teachable moment is a cueing event that increases perceptions of risk and outcome expectancies, prompts strong emotional responses and causes a redefinition of an individual's self-concept or social role (10,11) . According to McBride et al (11) , a disease diagnosis is considered a teachable moment because it may NHANES, National Health and Nutrition Examination Survey; IPR, income to poverty ratio; ref., reference category.…”
Section: Discussionmentioning
confidence: 99%
“…According to McBride et al (11) , a disease diagnosis is considered a teachable moment because it may NHANES, National Health and Nutrition Examination Survey; IPR, income to poverty ratio; ref., reference category. Individual-level data (n 5110) from NHANES 2005-2010 waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation